Condylar hyperplasia, approach to diagnosis and treatment. Review of the literature - Sedano Balbin, Gabriela (2019)
Condylar hyperplasia (HC) was first described by Robert Adams in 1836. This mandibular pathology presents several types that affect bone size and morphology, alter occlusion and dentolabial structures, indirectly affect the maxilla, resulting in facial patterns that can be characterized by: mandibular prognathism, unilateral increase of the condyle, neck, branch and body, facial asymmetry, temporomandibular joint dysfunction, neuromuscular imbalance and myofacial pain pathology. This condition of the HC, requires a multidisciplinary treatment, which according to its severity, is the responsibility of oral and maxillofacial surgeons, orthodontists, physiotherapists, plastic surgeons. The diagnosis of HC is based on the anamnesis, the clinical examination and the imaging evaluation, consisting of panoramic cephalometric radiographs, macizo-facial tomography (TEM CBCT), bone scintigraphy and in some cases anatomo-pathological study. The purpose of this review is to know in detail the behavior and prognosis of this pathology according to the type, in order to facilitate diagnosis and therapeutic options, according to the severity, the age of the patient and the pathology in its active form or inactive.